2009
DOI: 10.1177/0731684408100264
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Injection-molded Natural Fiber-reinforced Polypropylene Composites: Formulation and Compounding Processes

Abstract: In this study, the effects of material optimization and compounding processes on the properties of natural fiber composites were studied. The thermal stabilities of sisal fiber and jute fiber were compared by thermogravimetric analysis. The influences of fiber content, coupling agent, fiber geometry, and fiber distribution on the properties were also researched. It was observed that sisal fiber had more thermal stability than jute fiber. Addition of coupling agent, long fiber length, and uniform fiber distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…However, the increase of the tensile strength with the addition of PP‐g‐MA is reported in different publications, although the Young's modulus remains as expected unaffected. The increase of the tensile strength is attributed to an enhanced adhesion between the matrix and the fibers . Bledzki et al reported that the notched impact strength is not significantly affected by PP‐g‐MA at flax fiber contents from 20 wt% above, which corresponds with the results obtained in this study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, the increase of the tensile strength with the addition of PP‐g‐MA is reported in different publications, although the Young's modulus remains as expected unaffected. The increase of the tensile strength is attributed to an enhanced adhesion between the matrix and the fibers . Bledzki et al reported that the notched impact strength is not significantly affected by PP‐g‐MA at flax fiber contents from 20 wt% above, which corresponds with the results obtained in this study.…”
Section: Resultssupporting
confidence: 90%
“…So far, most scientific investigation of short flax fiber-reinforced PP composites focused on flax fiber or matrix modification using different chemical or physical pretreatments [1,7,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. These investigations show that treatment with maleic anhydride (MA) is one of the most effective methods and enhances in particular the tensile properties [1,7,[25][26][27][28][29][30][31][32][33][34][35]. Arbelaiz et al [25] showed that the modification of the polymer is more efficient than the fiber modification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical fiber length (l c ) of kenaf fiber in the PP matrix was estimated using the well-known Kelly and Tyson equation [32].…”
Section: Effects Of Processing On Fiber Length Distribution and Critimentioning
confidence: 99%
“…A number of studies have been reported on thermoset-plastics-natural fibre composites. Injection and extrusion moulding processes for fabrication of short fibre/thermoplastic composites are proficient and economic (Sun et al 2010;Paulo et al 2007). In extrusion moulding process, fibres are well distributed into a matrix which is most desirable for enhanced composite properties.…”
Section: Introductionmentioning
confidence: 98%